2012
DOI: 10.1136/bmj.e1257
|View full text |Cite
|
Sign up to set email alerts
|

Risk of atrial fibrillation and stroke in rheumatoid arthritis: Danish nationwide cohort study

Abstract: Objectives To determine if patients with rheumatoid arthritis have increased risk of atrial fibrillation and stroke.Design Longitudinal nationwide register based cohort study. Setting Main outcome measures Rates of atrial fibrillation and stroke.Results Of 4 182 335 participants included in the cohort, 18 247 were identified as having rheumatoid arthritis during follow-up, with a mean age at disease onset of 59.2 years and a median follow-up of 4.8 years. A total of 156 484 people, including 774 with rheumato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
109
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(127 citation statements)
references
References 41 publications
(47 reference statements)
8
109
1
3
Order By: Relevance
“…Moreover, large population-based studies seem to indicate that also the prevalence of atrial fibrillation is significantly higher in RA subjects than in the general population, suggesting that these patients are characterized by an abnormal diffuse myocardial electrical instability. Although the underlying mechanisms accounting for the pro-arrhythmogenic substrate in RA are probably intricate, the leading role seems to be played by chronic systemic inflammatory activation which is able to promote arrhythmias both indirectly, by accelerating the development of ischemic heart disease and congestive heart failure, and directly, by affecting cardiac electrophysiology [59,60]. Biomarkers associated with heart failure B-type natriuretic peptide (BNP) or N-terminal fragment of proBNP (NT-proBNP)…”
Section: Rheumatoid Arthritis and Heart Failurementioning
confidence: 99%
“…Moreover, large population-based studies seem to indicate that also the prevalence of atrial fibrillation is significantly higher in RA subjects than in the general population, suggesting that these patients are characterized by an abnormal diffuse myocardial electrical instability. Although the underlying mechanisms accounting for the pro-arrhythmogenic substrate in RA are probably intricate, the leading role seems to be played by chronic systemic inflammatory activation which is able to promote arrhythmias both indirectly, by accelerating the development of ischemic heart disease and congestive heart failure, and directly, by affecting cardiac electrophysiology [59,60]. Biomarkers associated with heart failure B-type natriuretic peptide (BNP) or N-terminal fragment of proBNP (NT-proBNP)…”
Section: Rheumatoid Arthritis and Heart Failurementioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common clinically relevant arrhythmia, with a wide range of potential complications, and contributes significantly to population morbidity and mortality 3. Large population‐based studies indicate that the prevalence of AF is significantly higher in RA patients than in the general population 4, 5, 6. The meta‐analysis of the pooled data from these studies demonstrated ≈30% statistically significant increased risk of AF in RA patients compared with participants without RA 7.…”
Section: Introductionmentioning
confidence: 99%
“…Stable exertional angina (go to qn A1.5)1 ACS: Unstable angina 8 (go to qn A1.7) ACS: STEMI 9 (go to qn A1.7)…”
Section: Discussionmentioning
confidence: 99%
“…moderate limitation 3 Inability to perform any activity without angina or angina at rest, i.e. severe limitation 4 Nuclear myocardial perfusion scan 3 MRI stress perfusion scan 4 Tick the appropriate combination Basal anterior 1 Basal anteroseptal 2 Basal inferoseptal 3 Basal inferior 4 Basal inferolateral 5 Basal anterolateral 6 Mid-anterior 7 Mid-anteroseptal 8 Mid-inferoseptal 9 Mid-inferior 10 Mid-inferolateral 11 Mid-anterolateral 12 Apical anterior 13 Apical Agatston score:…”
Section: Discussionmentioning
confidence: 99%